(untitled) (The Review of Diabetic Studies, 2025)
Healthcare systems are increasingly challenged by fragmented, department-centered care models that limit the effectiveness of patient management strategies. Redesigning patient care requires a shift toward integrated, multidisciplinary collaboration that aligns clinical, organizational, and support services around patient needs. This review aims to synthesize contemporary evidence on how multidisciplinary medical collaboration contributes to the redesign of patient care strategies and improves healthcare quality and outcomes. A comprehensive review of recent international literature was conducted across major healthcare and health services databases, focusing on studies that examined collaborative practices involving multiple medical departments and their influence on patient-centered strategy development. The synthesized evidence indicates that structured multidisciplinary collaboration enhances care coordination, reduces medical errors, improves clinical outcomes, and strengthens patient satisfaction and continuity of care. Key enabling factors include effective governance frameworks, shared decision-making processes, interoperable digital health systems, and workforce competencies that support interprofessional practice. Based on the integrated evidence, this review proposes a conceptual model illustrating the relationships between multidisciplinary collaboration mechanisms, redesigned patient care strategies, and patient- and system-level outcomes. The findings provide practical and policy-relevant insights for healthcare leaders seeking to implement sustainable, patient-centered strategies across complex healthcare systems.